"A labor of love": on the perils and seductions of writing about Iran. An Interview with Jill Worrall. Issue 3 (3rd July 2018) - Nazari, Hossein
ABSTRACT: In this interview conducted in 2016 In Christchurch, New Zealand, the award-winning New Zealand travel writer Jill Worrall discusses her book Two Wings of a Nightingale: Persian Soul, Islamic Heart (2011), which narrates her travel to Iran. The narrative recounts the expedition in which Worrall follows the ancient caravanserais routes across Iran with her Iranian guide, Reza, and offers insightful commentary on Iranian culture, history, literature, and arts. In this discussion Worrall delineates the process of writing her book, the many ways in which her travelogue attempts to challenge and subvert dominant stereotypes about Iran, and her disillusionment with a global publishing industry that seems more interested in perpetuating dehumanising Orientalist stereotypes about certain cultures, than in offering alternative perspectives.